Commentary on the Jumal on Logic by Khūnajī - al-Ḥamawī, Ibn Wāṣil (Islamic Philosophy, Theology and Science. Texts and Studies, 2022)
Ibn Wāṣil (d. 1298), perhaps better known today as a historian and an emissary to the court of King Manfred in southern Italy, was also an eminent logician. The present work is a critical edition of his main work in the field, a commentary on his teacher Khūnajī's (d. 1248) handbook al-Jumal. The work helped consolidate the logic of the "later scholars" (such as Khūnajī). It also shows that commentators did much more than merely explain the original work and instead regularly discussed and assessed received views. Ibn Wāṣil's work was an influential contribution to a particularly dynamic chapter in the history of Arabic logic.